AGE AND GENDER-SPECIFICS OF CARDIOVASCULAR MORTALITY IN HEMODIALYSIS PATIENTS - Shifris, I. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Cardiovascular diseases are the leading causes of death in hemodialysis (HD) patients. An analysis of the epidemiological evidence is the basis for the development of the measures and recommendations directed on reducing prevalence of fatal events, including cardiovascular. Aim. The study of cardiovascular mortality in patients who received treatment for renal replacement therapy, based on the demographic and gender characteristics, type of kidney damage and duration of HD treatment. Methods. Cardiovascular mortality causes in 89 patients who received programmed hemodialysis from January 1, 2007 to December 31, 2011 in Kyiv City Scientific and Practical Center of Nephrology and Dialysis were analyzed. Results. Cardiovascular disease was the primary cause of death in the study population (64, 96 %). The annual cardiovascular mortality rate has a significant positive trend in the HD patients. It was ascertained its declining from 10,26% in 2007 to 6,69% in 2011. About 40% of cardiovascular causes of death occurred during the first 90 days of HD treatment, 73,53% of them were among males. The number of fatality authentically is higher for younger women with non- diabetic renal glomerular lesions and middle-aged patients with diabetes mellitus. CVD, as the cause of death, was significantly more often for males of middle age with the glomerular (diabetic and non-diabetic) diseases and of the elderly - with nonglomerular and non-diabetic glomerular origin. Conclusion. According to the study the series of the regularities of the structure of cardiovascular mortality has been established. The significant association between the sex of the patient and the type of renal disease was identified in each age group.